Pengembangan UMKM Digital di Kota Blitar Pada Masa Pandemi Covid-19 - Hardining Estu Murdinar; Eni Susilowati; Firly Firly (Universitas Kadiri, 2022)
This article aims to elaborate on the development of Micro, Small and Medium Enterprises (MSMEs) during the Covid-19 pandemic. MSMEs as drivers of the domestic economy and absorber of labor face a decline in productivity which results in a significant decline in profits. Therefore, an entrepreneurial model is needed that can adapt to technological advances. This is what gave birth to the digital entrepreneurship model. There are four dimensions related to digital entrepreneurship, namely digital actors (who), digital activities (what), digital motivation (why) and digital organizations (how). This research uses a literature study approach by observing and analyzing all the information on the research topic. There are several obstacles faced by micro entrepreneurs in Blitar City to enter the digital market ecosystem, namely limited human resources in digital literacy, determining digital platforms, and digital marketing strategies. its operations changed, from selling physical stores to platforms on the internet. As a first step in starting digital marketing, it is important for SMEs to design creative content, so that the message they want to convey can be received by target consumers with an attractive impression. The Blitar City Government through the Office of Cooperatives and Micro Enterprises (UM) has provided guidance and motivation for micro business actors in the context of the National Economic Recovery (PEN) due to the Covid-19 Pandemic. As well as providing some training for micro-enterprises. Starting from product packaging design training to online marketing.